Augmentation of Biogas Production Efficiency Under Different Feeding Interval of Waste Products - Nipa, Most Sharmin Sultana; Khan, Muckta; Ryndin, Roman; Islam, M. Alimul; Kabir, Humayun (Journal of the Bangladesh Agricultural University, 2024)
Biogas originates from bacteria in the process of biological breakdown of organic material under anaerobic conditions. Biogas can be produced from biodegradable substrates such as agricultural waste, cow dung, municipal waste, plant material, sewage, green waste or food waste. The study was conducted to augment biogas production efficiency under different feeding interval. The objectives were measured biogas production, estimate major components (Ambient Temperature, pH, CH4, CO2), measure the biogas production efficiency under different ambient temperature and pH. Two digesters were installed to digest cow dung, where one set-up was used for digestion of cow dung by regular feeding and other set-up was used for digestion by 4-day interval feeding. The digester was made up of PVC of 7.5 m3 capacity while gas holding capacity was 2 m3. 50kg cow dung and 50 L water was used at 1:1 ratio for regular feeding. In 4-day interval, 200 kg cow dung and 200 L water was used at 1:1 ratio. The digesters were operated at ambient temperature 25-350C. The pH ranges from 6.5-7.5. The ambient temperature and pH maintained good range for gas production. The overall biogas yield for feeding in 4-day interval was 34% higher compared to regular feeding as well as there was a significant difference from regular feeding. The methane yield was 28% more in 4-day interval feeding. 48 kg of cow dung would be necessary to produce 1 m3 of biogas in praxis as usual and 32 kg feeding in 4-day interval. In both setups, the digesters could produce enough biogas to cover daily theoretical demand (0.8-1.6 m3) for preparing 2 meals for the average family size in Bangladesh. J Bangladesh Agril Univ 19(1): 134–142, 2021 https://doi.org/10.5455/JBAU.17256